Theoretical substantiation of the necessity of formation of scientific-methodological competence of teachers in the system of postgraduate pedagogical education - Tolochko, Svitlana; Ridey, Natalia (ScienceRise: Pedagogical Education, 2017)
During the study we determined contradictions that influence the development of postgraduate pedagogical education in Ukraine. The notions “methodical competence”, “learning-methodical competence” and “scientific methodical competence” were concretized. This research favors the theoretical-methodological analysis of the predominant paradigm of interpretation of pedagogical education, able to correspond to challenges of full-life activity and self-perfection for the personal formation, the necessity of teachers’ scientific-methodical competence formation. The structure of the scientific-methodical competence, formed in the process of increasing base knowledge, abilities and competences of a scientific-pedagogical worker and favors his/her personal style and own staff-technology and consists of the scientific, scientific-research work, learning-scientific-innovative activity, using modern informational learning technologies, scientific diagnostic, expertise was determined